(untitled) (Bioagro, 2018)
Considering the potential for the urban tree planting of dry tropical areas of Pithecellobium dulce (Roxb.) Benth and Platymiscium diadelphum S.F. Blake and the importance of the container on the initial growth and conformation of the roots in woody plants, sowing and transplantation were studied in both species in two types of conical containers (designed to produce forestry plants). The treatments consisted of (T1): seeds propagated by seeding in conical tubes; (T2): seeds sown in tubes for pivoting roots; and (T3): seeds sown as in T1 and later transplanted to the same container used in T2. The evaluations were started 30 days after the start of the trial and extended for 90 days, determining the following variables: height of the plant, stem diameter, number of leaves, leaf area, relative chlorophyll index, length of roots, dry mass of aerial part and roots. The data allowed to calculate the ratio of dry mass of aerial part/roots, slenderness index, and Dickson index. These biometric variables and morphological indices were used to quantitatively and qualitatively characterize the growth of both species, which indicated that the plants meet the quality characteristics and potential for transplant survival during the evaluation period. The T3 favored the best distribution, arrangement and conformation of the root ball.